The Ubiquity and Potency of Labeling in Organizations - Ashforth, Blake E.; Humphrey, Ronald H. (Organization Science, 1997)
Drawing on categorization theory, semiotics, and labeling theory, we argue that categories and labels are widely utilized by individuals in organizational settings to help structure and simplify the social environment, primarily for reasons of understanding, consensus, and control. Based largely on such situational criteria as role and rank, people are sorted into various categories and are perceived and treated as exemplars or prototypes of the category. The labels attached to these categories coalesce when individuals triangulate their perceptions of category members with the perceptions that credible peers and powerholders have of category members. Labels distill a complex and perhaps contradictory array of data into concise and coherent packages, and thus provide a potent means of interpreting, representing, and conveying organizational experience and cuing action. However, labels are inherently arbitrary, labels cause individual category members to lose their individuality and assume the affective tone of the category, and labels tend to become reified as objective and normative accounts of social reality. The ubiquity and potency of labeling processes are illustrated with applications to individual-level (service encounters), group- level (intergroup conflict), and organization-level (identity, image, and reputation) phenomena. We speculate that both the process of labeling and the content of labels are similar across levels.